The Influence of Taste and Price on Consumer Satisfaction - Ade Perdana Siregar; Nofirman Nofirman; Muhammad Yusuf; Imam Jayanto; Sri Rahayu (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to analyze the influence of taste and price on consumer satisfaction at a western fast food restaurant. The research design used in this study used quantitative associative methods. Based on the results of data analysis that has been carried out on the first hypothesis (H1) which states that taste has a positive and significant effect on consumer satisfaction, the t-count value is 22,984 which is greater than the t-table value of 1.661, testing the second hypothesis (H2) which states that price has a positive and significant effect on consumer satisfaction, the t-count value is 23,908, which is greater than the t-table value of 1.661, which means that taste and price have a positive and significant effect on consumer satisfaction, while the R-square value obtained is 0.865 which states that the taste and price variables affect consumer satisfaction by 86.50% and the remaining 13.50% is influenced by other variables.